Conflict Style of Rohingya Refugee Rejection in Aceh from Face Negotiation Approach - Falcao Falcao; Niken Febrina Ernungtyas (Journal La Sociale, 2024)
Rohingya refugees in Indonesia were previously welcomed with open arms. However, recently there has been a rejection of the presence of Rohingya refugees in Aceh, both those already in refugee camps and those who just want to dock on the coast of Aceh. This transnational cultural conflict indicates the failure of the communication and interaction process between the two cultures. By applying and extending the face-negotiation theory (FNT) that explains the management style of intercultural conflict, this study explores the case of Rohingya refugee rejection in Aceh with FNT using the content analysis method of media coverage in Indonesia. The purpose of this research is to assess and identify the conflict management styles of the stakeholders in the case. As a result, the government and parliament at the central level tend to display an integrating style, while the government in Aceh and DPRA tend to show an avoiding style, while community leaders and Acehnese citizens who are directly dealing with Rohingya refugees tend to dominate.